Implementasi Nilai-Nilai Pancasila Serta Peran Manajemen Security dalam Memperkuat Keamanan dan Ketahanan Budaya di Universitas Bhayangkara Jakarta Raya - Jiwa Banyu Semesta Joned; Edy Soesanto; Salsabila Putri Setiawan (International Forum of Researchers and Lecturers, 2024)
Bhayangkara University, Jakarta Raya (UBJ) as a higher education institution has an important role in instilling Pancasila values and strengthening security and cultural resilience among the younger generation. Implementation of Pancasila values at UBJ is important in efforts to build a nation's character with morals and integrity. Implementation of Pancasila values at UBJ can be done in various ways, such as: organizing a cultural festival that displays various arts and culture from several regions in Indonesia, education about Pancasila values for UBJ academics, and community service which aims to spread the values -Pancasila values and strengthening cultural resilience in society. Good security management also plays an important role in supporting the implementation of Pancasila values and strengthening security and cultural resilience at UBJ. In an effort to ensure this implementation runs well, security management plays an important role in creating a safe and conducive campus environment, so that UBJ academics can focus on learning and teaching in peace. These efforts are expected to increase understanding and practice of Pancasila values among UBJ academics, as well as strengthen security and cultural resilience at UBJ. This effort needs to be carried out continuously and systematically in order to achieve optimal results.